THE EFFECT OF THERAPEUTIC COMMUNICATION ON THE LEVEL OF ANXIETY IN PREOPERATIVE PATIENTS - aprillya sekararum, dewi; Nur Alpiah, Dini (International Journal of Social Research, 2025)
Surgery is a treatment procedure that uses invasive techniques by opening the part of the body to be treated with an incision which ends with stitching the wound. Of course, patients who will undergo surgery will feel anxious. Therefore, therapeutic communication will be used to reduce patient anxiety. Therapeutic communication is health communication that can provide accurate information and increase the confidence of patients who will undergo surgery. Therefore, every hospital nurse must have good therapeutic communication skills. Adding therapeutic communication skills to nurses can be done through workshops and other training. The design of this research is a literature review or also known as a systematic method for carrying out identification and evaluation of works from the results of research conducted by previous researchers. Using 5 journals covering the last 10 years.The results of this study found that 5 journals said that good therapeutic communication was related to reducing anxiety in preoperative patients with a p-value <0.005.